Pengaruh Brand Awareness dan Electronic Word of Mouth Marketing terhadap Repurchase Intention melalui Costumer Satisfaction sebagai Variabel Intervening pada Fashion Erigo di Aplikasi Shopee: Studi Kasus pada Mahasiswa Fakultas Ekonomi dan Bisnis, Universitas Negeri Makassar - Mohammad Fadel Astari; Chalid Imran Musa; Muhammad Ilham Wardana Haeruddin; Muhammad Ichwan Musa; Zainal Ruma (JURNAL RISET MANAJEMEN (JURMA), 2024)
This research aims to determine the influence of Brand Awareness and Electronic Word of Mouth Marketing on Repurchase Intention through Customer Satisfaction as an Intervening Variable in Erigo Fashion in the Shopee Application on Students of the Faculty of Economics and Business, Makassar State University. The data used in this research is primary data of 100 samples. This type of research is included in quantitative research. The population in this study were students from the Faculty of Economics and Business, Makassar State University who had made purchases from Erigo Fashion on the Shopee Application. Data collection was carried out using documentation and survey methods using questionnaires. The data analysis technique uses PLS (Partial Least Square) analysis. The results of this research show that brand awareness and electronic word of mouth have a positive and significant influence on customer satisfaction with Erigo fashion in the Shopee application. Furthermore, customer satisfaction also has a positive and significant impact on repurchase intention. Brand awareness does not have a significant influence on repurchess intention, and electronic word of mouth does not have a significant influence on prepurchess intention. Apart from that, brand awareness influences repurchase intention through customer satisfaction as an intervening variable, while electronic word of mouth also influences repurchase intention through customer satisfaction as and intervening variable.